Developing Synodality at the Diocesan and Parish Levels - Kheng, Christina (Asian Horizons, 2025)
Synodality characterizes the way of being and proceeding as Church. However, the lived experiences of many local churches around the world are sometimes far from this ideal. It is thus crucial that intentional efforts are made to develop synodality especially at the diocesan and parish levels where the majority of the baptized live out their faith. This article offers a framework for cultivating synodality in a comprehensive, holistic, and sustained way in local churches. It highlights key areas for implementation including reshaping formation for clergy, religious, and laity, facilitating associations among the faithful, promoting co-responsibility in ministry and leadership, building bridges to marginalized groups and to the wider society, ensuring consultation and communal discernment, and renewing liturgies. The article points out crucial shifts that are required in attitudes and ecclesial cultures, and offers practical suggestions for taking concrete steps forward.